2003
DOI: 10.1177/0095798403256893
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Marijuana Use and Psychosocial Behaviors at Two Historically Black Universities

Abstract: Research exploring marijuana use patterns in students at historically Black colleges and universities (HBCUs)is relatively sparse. This study sought to empirically assess three constructs (resilient, invulnerable, and vulnerable)as they relate to marijuana use and to assess the role of spirituality and social support as potential buffering mechanisms. Participants in this study were 1,013 African American undergraduate students from two HBCUs in the mid-Atlantic region of the United States. Participants comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…These findings expand on previous research on college students' marijuana use conducted at HBCUs. Past investigations (see Bowen-Reid & Rhodes, 2003;Rhodes et al, 2008) have found that marijuana use and marijuanaimpaired driving occurred on HBCU campuses; however, our findings extend this line of inquiry by identifying possible risk profiles, based on a set of variables, of students who engage in these behaviors. These emerging profiles can provide college counselors with greater insight into possible prevention, early intervention, and treatment strategies.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…These findings expand on previous research on college students' marijuana use conducted at HBCUs. Past investigations (see Bowen-Reid & Rhodes, 2003;Rhodes et al, 2008) have found that marijuana use and marijuanaimpaired driving occurred on HBCU campuses; however, our findings extend this line of inquiry by identifying possible risk profiles, based on a set of variables, of students who engage in these behaviors. These emerging profiles can provide college counselors with greater insight into possible prevention, early intervention, and treatment strategies.…”
Section: Discussionsupporting
confidence: 59%
“…Approximately one fourth (23.8%) of students reported smoking marijuana within the past 30 days, and roughly one in 10 (9.1%) participants reported smoking marijuana 20 or more times in the past 30 days. These percentages are elevated compared to research across other HBCUs (Bowen-Reid & Rhodes, 2003;Rhodes et al, 2008).…”
Section: Sample Representativenessmentioning
confidence: 64%
See 3 more Smart Citations